2008
DOI: 10.1186/1477-3155-6-1
|View full text |Cite
|
Sign up to set email alerts
|

N-hexanoyl chitosan stabilized magnetic nanoparticles: Implication for cellular labeling and magnetic resonance imaging

Abstract: This project involved the synthesis of N-hexanoyl chitosan or simply modified chitosan (MC) stabilized iron oxide nanoparticles (MC-IOPs) and the biological evaluation of MC-IOPs. IOPs containing MC were prepared using conventional methods, and the extent of cell uptake was evaluated using mouse macrophages cell line (RAW cells). MC-IOPs were found to rapidly associate with the RAW cells, and saturation was typically reached within the 24 h of incubation at 37°C. Nearly 8.53 ± 0.31 pg iron/cell were bound or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 13 publications
(17 reference statements)
4
27
0
1
Order By: Relevance
“…After 6 hours, 200 mg of pluronic polymer F68 (average molecular weight 8350) in 5 mL water was added to the nanoparticle suspension and stirred overnight. After five washes with water, 33 the nanoparticles were resuspended in 25 mL water and centrifuged at 1000 rpm to remove larger aggregates. This formulation was designated as MNP.…”
Section: Preparation Of Mnp and Mnp-cur Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 6 hours, 200 mg of pluronic polymer F68 (average molecular weight 8350) in 5 mL water was added to the nanoparticle suspension and stirred overnight. After five washes with water, 33 the nanoparticles were resuspended in 25 mL water and centrifuged at 1000 rpm to remove larger aggregates. This formulation was designated as MNP.…”
Section: Preparation Of Mnp and Mnp-cur Formulationsmentioning
confidence: 99%
“…The drug-loaded nanoparticles were washed three times by resuspending them in water and separated with the help of magnets. 33 These drug-loaded nanoparticles were dispersed in 2 mL sterile phosphate buffered saline (PBS) solution and stored in a refrigerator until further use. This formulation was designated as MNP-CUR.…”
Section: Preparation Of Mnp and Mnp-cur Formulationsmentioning
confidence: 99%
“…However, there are not many reports on detailed studies of the growth process of monodispersed superparamagnetic iron oxide nanoparticles (SPIONs), although the syntheses of relatively uniform magnetite and maghemite nanoparticles have been reported. 8 It was observed that the wet chemical method for iron oxide nanoparticles is advantageous since it was a method to produce under 10 nm particles.…”
Section: Introductionmentioning
confidence: 99%
“…where the shift is due to the addition of vibration from O -H [24]. Based on the FTIR data, in combination with the elemental analysis, we believed that the most likely component of the nanoparticles was glycoprotein, owing to the shared amide II band with the BSA spectrum, and the shared CO-C band with the chitosan spectrum.…”
Section: Chemical Analysis Of the Ivy Nanoparticlesmentioning
confidence: 94%